Cosmological Evolution of Pilgrim Dark Energy in f(G) Gravity - Abdul Jawad; Shamaila Rani (Advances in High Energy Physics)
We analyze the behavior of pilgrim dark energy with Hubble horizon in f(G) gravity. We reconstruct the f(G) models through correspondence phenomenon by assuming two values of pilgrim dark energy parameter (u=2, -2). We evaluate the equation of state parameter which shows evolution of the universe in the quintessence, vacuum, and phantom phase for both cases of u and give favor the pilgrim dark energy phenomenon. Also, squared speed of sound exhibits the stability of f(G) model for both cases of u. The wPDE-wPDE′ also provides freezing and thawing regions in this scenario. In this framework, the r-s plane also corresponds to different dark energy scenarios.